2020
DOI: 10.29024/joa.29
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Does the Open Access Status of Articles Predict Their Social Media Visibility? A Case Study of Life Sciences and Biomedicine

Abstract: This study aimed to determine whether, and to what extent, the OA status and OA type of articles can predict their social media visibility, when controlling for a considerable number of important factors. Those factors, which previous research confirmed their positive association with altmetric counts, were journal impact, individual collaboration, research funding, number of MESH topics, topic, international collaboration, lay summary, being a mega journal, F1000 Score, and gender of first and last authors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…This finding is interesting as it might show the potential role of open access in fast dissemination of the scientific research in Climate Action to a broader community via news outlets. The finding with regard the news count advantage of OA papers is in line with Dehdarirad and Didegah (2020) for articles in life science and biomedicine, and Holmberg et al (2020), who found OA news count advantage in some fields in Finish research publications.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This finding is interesting as it might show the potential role of open access in fast dissemination of the scientific research in Climate Action to a broader community via news outlets. The finding with regard the news count advantage of OA papers is in line with Dehdarirad and Didegah (2020) for articles in life science and biomedicine, and Holmberg et al (2020), who found OA news count advantage in some fields in Finish research publications.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding journal characteristics, journal impact as SNIP (Source Normalized Impact per Paper) and being a mega journal were considered, as they have been shown to be important factors for altmetrics counts (Didegah et al, 2018;Dehdarirad & Didegah, 2020;Dehdarirad, 2020). For each article, the SNIP values were downloaded from SciVal.…”
Section: Journal-related Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparison of one gold OA physics journal to one paywalled physics journals, Robinson-García et al (2018) found that gold OA articles received a mean of 1.22 news and blog mentions, more than paywalled (a mean of 0.23 news and blog mentions) and green OA (0.22 news and blog mentions), although it did not separate out news mentions from blog posts. A study of life sciences and biomedicine articles found both a positive correlation for the OA status of an article when looking at the likelihood of an article receiving any news mention and the number of news mentions received (Dehdarirad & Didegah, 2020).…”
Section: News Coverage Of Oa Researchmentioning
confidence: 99%
“…A study on 1761 Nature Communications articles demonstrates that OA articles received more citations and page views, more numbers downloads over a longer period, and also draws more social media attention (Twitter and Facebook) as compared to non‐OA articles (Emery et al, 2021; Wang et al, 2015). Another article shows that a paper being open makes the probability of the paper being mentioned on the social media platforms used in the study (Dehdarirad & Didegah, 2020). Since literature studies support OA papers' more significant visibility theory, it is safe to assume that Indian authors can draw more attention towards their research by self‐archiving their papers in IR even if they publish in subscription/hybrid journals instead of paying APC.…”
Section: Discussionmentioning
confidence: 99%